Efektifitas Bahan Ajar Program MAULANA Metode ADaBTa dalam Percepatan Literasi Dasar Membaca Siswa Madrasah Ibtida'iyah Kecamatan Suralaga - Dewi Rohiani; Mukminah Mukminah; Janniatin Rusmaeni (STKIP Pesisir Selatan, 2024)
The effectiveness of teaching materials for the MAULANA (Superior Madrasah for Great Children) ADaBTa method in accelerating students' basic reading literacy in Suralaga District, East Lombok Regency. The approach used in this research is a quantitative approach. The population in this study were madrasas in Suralaga District, while the sample in this study was eleven madrasas in Suralaga District. The data collection instrument is a reading ability test. Meanwhile, data analysis uses descriptive statistics. The research results show that the number of students who experienced a level increase in group one, namely beginner level, seen from the percentage of pretest and posttest scores, was 41.81% to 11.68% and at the letter level from 15.79% to 19.16%. Meanwhile in group two, namely at the word level from 11.26% to 23.65% and at the sentence level from 11.84% to 15.12%. Meanwhile at the paragraph and story level from 19.30% to 30.39%. So, the MAULANA program teaching materials using the ADABTa Method are effective in accelerating students' basic reading literacy in Suralaga District, East Lombok Regency, this can be seen from the increase in the percentage of each group at each level.